2017
DOI: 10.1136/oemed-2017-104384
|View full text |Cite|
|
Sign up to set email alerts
|

High exposure to endotoxin in farming is associated with less new-onset pollen sensitisation

Abstract: High exposure to endotoxin during young adulthood appears to protect against new onset of pollen sensitisation, independent of childhood farm exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Analyses were based on exposure quartiles, the 4th quartile representing the highest exposure. 8,9 Changes in Table 1 show less newonset sensitization to Lep d among participants with a rural or farm childhood and a greater loss of sensitization consistent with findings for other aeroallergens. 8 In contrary, farming exposure during adulthood appeared to be consistently associated with increased new- Figure S1 shows the results of the adjusted SPT analyses).…”
Section: Adult Farming Exposure Does Not Protect Against Sensitizatiosupporting
confidence: 69%
See 2 more Smart Citations
“…Analyses were based on exposure quartiles, the 4th quartile representing the highest exposure. 8,9 Changes in Table 1 show less newonset sensitization to Lep d among participants with a rural or farm childhood and a greater loss of sensitization consistent with findings for other aeroallergens. 8 In contrary, farming exposure during adulthood appeared to be consistently associated with increased new- Figure S1 shows the results of the adjusted SPT analyses).…”
Section: Adult Farming Exposure Does Not Protect Against Sensitizatiosupporting
confidence: 69%
“…This protective effect was, however, not seen for HDM, but neither was an increased risk of new HDM sensitization among current farmers, 7 show high homology and mutual cross-reactivity but share only approximately 40% amino acid identity with Der p 2, and cross-reactivity with HDM does not appear as often as previously suspected. 10,11 In this study, we could determine both the HDM and 8 We speculate that this effect is due to a high occupational exposure to storage mites in general when working on a farm. While for the common allergens, exposure levels presumably remain relatively constant in adulthood as in childhood and adolescence, it is probable that the levels of general storage mite exposure increase considerably for young adults who start working as farmers.…”
Section: Adult Farming Exposure Does Not Protect Against Sensitizatiomentioning
confidence: 90%
See 1 more Smart Citation
“…The effects of exposure to endotoxin are predominantly respiratory, including decline in lung function and increased prevalence of chronic bronchitis and asthma-like syndrome [ 5 , 14 , 15 ]. In addition to adverse health effects, occupational endotoxin exposure in agricultural workers has also been implicated in protective effects on allergic sensitisation and hay fever [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For children, an inverse association between livestock exposure and allergic diseases has been firmly established, this protective association is believed to be mediated by exposure to microbes (Campbell et al, 2015). Recent studies also identified this inverse association in adult populations (adjusted for childhood farm exposure) suggesting continuous exposure to be the most effective to prevent development of allergic diseases (Elholm et al, 2013(Elholm et al, , 2018Smit et al, 2010;Spierenburg et al, 2017). For both atopic sensitization as asthma, the prevalence ratio observed in our study was substantial (0.75, 0.80; respectively) suggesting the size of the effect of livestock-related environmental exposure in a nonfarming population to be considerable.…”
Section: Endotoxin and Healthmentioning
confidence: 98%